Genome‐wide association study and meta‐analysis in Northern European populations replicate multiple colorectal cancer risk loci. Issue 3 (12th October 2017) - Tanskanen, Tomas; van den Berg, Linda; Välimäki, Niko; Aavikko, Mervi; Ness‐Jensen, Eivind; Hveem, Kristian; Wettergren, Yvonne; Bexe Lindskog, Elinor; Tõnisson, Neeme; Metspalu, Andres; Silander, Kaisa; Orlando, Giulia; et al.
Abstract : Genome‐wide association studies have been successful in elucidating the genetic basis of colorectal cancer (CRC), but there remains unexplained variability in genetic risk. To identify new risk variants and to confirm reported associations, we conducted a genome‐wide association study in 1, 701 CRC cases and 14, 082 cancer‐free controls from the Finnish population. A total of 9, 068, 015 genetic variants were imputed and tested, and 30 promising variants were studied in additional 11, 647 cases and 12, 356 controls of European ancestry. The previously reported association between the single‐nucleotide polymorphism (SNP) rs992157 (2q35) and CRC was independently replicated ( p = 2.08 × 10 −4 ; OR, 1.14; 95% CI, 1.06–1.23), and it was genome‐wide significant in combined analysis ( p = 1.50 × 10 −9 ; OR, 1.12; 95% CI, 1.08–1.16). Variants at 2q35, 6p21.2, 8q23.3, 8q24.21, 10q22.3, 10q24.2, 11q13.4, 11q23.1, 14q22.2, 15q13.3, 18q21.1, 20p12.3 and 20q13.33 were associated with CRC in the Finnish population (false discovery rate < 0.1), but new risk loci were not found. These results replicate the effects of multiple loci on the risk of CRC and identify shared risk alleles between the Finnish population isolate and outbred populations. Abstract : What's new? Genetic studies in isolated populations help characterize monogenic diseases and are being used more and more for the genetic analysis of complex diseases. Here, the authors performed a genome‐wide association study with Finnish individuals afflicted with colorectal cancer. They confirm a previously reported association of a single‐nucleotide polymorphism (rs992157) on chromosome 2q35, a finding independently replicated in a meta‐analysis of European‐ancestry individuals. Although no new risk loci were identified, the study underscores the importance of founder populations in the genetic evaluation of disease susceptibility.